2009
DOI: 10.3748/wjg.15.1409
|View full text |Cite
|
Sign up to set email alerts
|

Is transient elastography a useful tool for screening liver disease?

Abstract: Transient elastography (TE) is a new non invasive tool for measuring liver stiffness, which is correlated to the histologic stage of liver fibrosis. Several studies in chronic liver disease (CLD) have determined a good accuracy of TE in predicting significant fibrosis and an optimal accuracy in predicting cirrhosis. Normal liver stiffness ranges between 3.3-7.8 KPa and using a cut off of 7.1 KPa, significant fibrosis and cirrhosis can be excluded with a very high negative predictive value (NPV). Positive predi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 33 publications
1
22
0
1
Order By: Relevance
“…A recent prospective and longitudinal study also demonstrated the association between liver stiffness and HCC development in patients with chronic hepatitis C [24]. LSM had the potential indication of systemic screening of populations at high risk of chronic liver disease [25]. In our study, LSM was demonstrated useful in stratifying high-risk group of HCC presence in cirrhosis patients.…”
Section: Discussionsupporting
confidence: 67%
“…A recent prospective and longitudinal study also demonstrated the association between liver stiffness and HCC development in patients with chronic hepatitis C [24]. LSM had the potential indication of systemic screening of populations at high risk of chronic liver disease [25]. In our study, LSM was demonstrated useful in stratifying high-risk group of HCC presence in cirrhosis patients.…”
Section: Discussionsupporting
confidence: 67%
“…The method has been evaluated extensively in patients with chronic hepatitis C infection [15][16][17][18][19]. It was recently demonstrated, that the degree of liver stiffness measured by TE in CP patients with concomitant cholestasis was correlated with the histologically indicated stage of liver fibrosis [6].…”
Section: Discussionmentioning
confidence: 99%
“…Noninvasive markers are increasingly used for the assessment of liver fibrosis, such as serum biomarkers and transient elastography (TE). TE was originally developed to measure the stage of liver fibrosis by assessing the stiffness of the liver in a noninvasive manner through the use of ultrasonography in cases of chronic hepatitis C infection [15][16][17][18][19]. TE has been demonstrated to be a suitable method to reveal the severity of liver fibrosis in CP and concomitant cholestasis through measurement of the liver stiffness [6].…”
Section: Introductionmentioning
confidence: 99%
“…Liver fibrosis should not be assessed by TE in pregnant women and in patients with cardiac pacemaker [17].…”
Section: Examination Techniquementioning
confidence: 99%